Evidence based perioperative optimization of patients with obstructive sleep apnea in resource limited areas: A systematic review. (2020) - Melesse, Debas Yaregal; Mekonnen, Zemenay Ayinie; Kassahun, Habtamu Getinet; Chekol, Wubie Birlie
Abstract: Background: Obstructive sleep apnea is a syndrome characterized by periodic, partial, or complete obstruction in the upper airway during sleep. This, in turn, causes repetitive arousal from sleep to restore airway patency, which may result in daytime hyper somnolence or other daytime manifestations of disrupted sleep such as aggressive or distractible behavior in children. Obstructive sleep apnea syndrome is a complex disorder with series physiological consequences. Patients with obstructive sleep apnea syndrome have an increased tendency for upper airway obstruction during sleep, which leads to repetitive apnea, excessive daytime sleepiness and increased cardiovascular morbidity. Methods: This systematic review was conducted according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) protocol. Search engines like PubMed through HINARI, Cochrane database, Google Scholar to get access for current and updated evidences on perioperative anesthetic management for patients with obstructive sleep apnea. Discussion: Patients with a diagnosis of obstructive sleep apnea should be considered to be at increased risk for perioperative complications. Patients who had obstructive sleep apnea and at risk for obstructive sleep apnea should be identified before Surgery. The most effective and widely used treatment for obstructive sleep apnea is continuous positive airway pressure, it treats apnea –hypopnea by providing air under positive pressure through a nasal or facial mask thus creating a pneumatic splint in the pharynx, which prevents collapse of the pharyngeal airway. Conclusion: Patients with obstructive sleep apnea (OSA) who underwent procedures under anesthesia were at increased risk for perioperative complications compared with patients without the disease. The equipment for management of a difficult airway should be in place before induction of general anesthesia. Orotracheal tubes in various sizes, gum elastic bougie as well as a McCoy laryngoscope and a laryngeal mask airway were necessary. Highlights: Patients with obstructive sleep apnea are at increased risk for perioperative complications. Obstructive sleep apnea and its severity can be screened by STOP-BANG scoring system. A continuous positive airway pressure was recommended in symptomatic obstructive sleep apnea patients. Adenotonsilar hypertrophy and increased airway resistance were some of risk factors of obstructive sleep apnea.